Histone H2A deubiquitinases in the transcriptional programs of development and hematopoiesis: a consolidated analysis. (April 2023) - Wang, HanChen; Langlais, David; Nijnik, Anastasia
Abstract: Monoubiquitinated lysine 119 of histone H2A (H2AK119ub) is a highly abundant epigenetic mark, associated with gene repression and deposited on chromatin by the polycomb repressor complex 1 (PRC1), which is an essential regulator of diverse transcriptional programs in mammalian development and tissue homeostasis. While multiple deubiquitinases (DUBs) with catalytic activity for H2AK119ub (H2A-DUBs) have been identified, we lack systematic analyses of their roles and cross-talk in transcriptional regulation. Here, we address H2A-DUB functions in epigenetic regulation of mammalian development and tissue maintenance by conducting a meta-analysis of 248 genomics datasets from 32 independent studies, focusing on the mouse model and covering embryonic stem cells (ESCs), hematopoietic, and immune cell lineages. This covers all the publicly available datasets that map genomic H2A-DUB binding and H2AK119ub distributions (ChIP-Seq), and all datasets assessing dysregulation in gene expression in the relevant H2A-DUB knockout models (RNA-Seq). Many accessory datasets for PRC1–2 and DUB-interacting proteins are also analyzed and interpreted, as well as further data assessing chromatin accessibility (ATAC-Seq) and transcriptional activity (RNA-seq). We report co-localization in the binding of H2A-DUBs BAP1, USP16, and to a lesser extent others that is conserved across different cell-types, and also the enrichment of antagonistic PRC1–2 protein complexes at the same genomic locations. Such conserved sites enriched for the H2A-DUBs and PRC1–2 are proximal to transcriptionally active genes that engage in housekeeping cellular functions. Nevertheless, they exhibit H2AK119ub levels significantly above the genomic average that can undergo further increase with H2A-DUB knockout. This indicates a cooperation between H2A-DUBs and PRC1–2 in the modulation of housekeeping transcriptional programs, conserved across many cell types, likely operating through their antagonistic effects on H2AK119ub and the regulation of local H2AK119ub turnover. Our study further highlights existing knowledge gaps and discusses important directions for future work.